Analisis Kepuasan Pengguna Website Asuransi Untuk Peningkatan Pelayanan Asuransi Studi Kasus www.Cakrawalaproteksi.Com - Syafitri Mona Sari; Firdaus Firdaus; A. Haidar Mirza (Jurnal Nasional Ilmu Komputer, 2020)
Currently, technology has developed quite rapidly and covers all aspects, including in the insurance industry. Almost every insurance company has a website or social media that can be accessed by all internet users as a means of promotion and transactions. PT. Asuransi Cakrawala Proteksi is an insurance company that also carries out promotions through websites and social media. This research will discuss the customer satisfaction of PT. Asuransi Cakrawala Protection with the role of social media. Customer satisfaction is determined by looking at the difference between the actual value received and the expected value using the website and social media Facebook. From calculating the level of customer satisfaction with ServQual dimensions and simple analysis, a strategy will be produced to maintain or increase customer satisfaction.